Botulinum toxin in orofacial harmonization (Research, Society and Development, 2023)
Facial and body aesthetic procedures are becoming more and more popular due to the search for symmetry and perfection. In this context, botulinum toxin (BT) has emerged as an effective option for facial rejuvenation and harmonization. Its mechanism of action consists of promoting flaccid and transient neuromuscular paralysis through chemical denervation. There are seven different serotypes of TB, with botulinum toxin A (BTA) being the most used in facial aesthetic procedures. This work aimed to carry out a comprehensive narrative review on the use of botulinum toxin in the field of facial aesthetics. The results of clinical studies and recent research were analyzed to evaluate the effectiveness of botulinum toxin in reducing wrinkles and facial rejuvenation, in addition to investigating possible side effects and complications associated with its use. The rationale for this research is based on the growing demand for minimally invasive and long-lasting facial aesthetic procedures. Botulinum toxin has proven to be an effective option in this regard, but an updated scientific basis is needed to provide reliable information to health professionals and patients interested in this type of aesthetic treatment.